2015
DOI: 10.1152/japplphysiol.01128.2014
|View full text |Cite
|
Sign up to set email alerts
|

Spinal segment-specific transcutaneous stimulation differentially shapes activation pattern among motor pools in humans

Abstract: Transcutaneous and epidural electrical spinal cord stimulation techniques are becoming more valuable as electrophysiological and clinical tools. Recently, we observed selective activation of proximal and distal motor pools during epidural spinal stimulation. In the present study, we hypothesized that the characteristics of recruitment curves obtained from leg muscles will reflect a relative preferential activation of proximal and distal motor pools based on their arrangement along the lumbosacral enlargement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
97
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(108 citation statements)
references
References 54 publications
8
97
1
2
Order By: Relevance
“…Participants provided written informed consent to the experimental procedures, which were approved by the local institutional review board. Detailed description of the transcutaneous electrical spinal cord stimulation protocol has been reported [25]. During the experiment, the participants stayed relaxed in a supine position.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants provided written informed consent to the experimental procedures, which were approved by the local institutional review board. Detailed description of the transcutaneous electrical spinal cord stimulation protocol has been reported [25]. During the experiment, the participants stayed relaxed in a supine position.…”
Section: Methodsmentioning
confidence: 99%
“…We recently demonstrated that transcutaneous electrical spinal cord stimulation can be used to differentially activate dorsal roots and corresponding motor pools based on their anatomical arrangements along the rostro-caudal axis of the lumbosacral enlargement [25]. In light of the spatial arrangement of the motor pools and networks along the lumbosacral enlargement (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…We have characterized the relative selectivity of recruitment of different motor pools innervating leg muscles in non-injured subjects by using transcutaneous stimulation along the rostro-caudal axis of the lumbosacral enlargement (Fig. 3), at sites similar to a previous study with epidurally implanted electrodes [16]. Variation in many characteristics of the evoked potentials reflects a relative preferential activation of proximal and distal leg muscles based on the rostro-caudal position of the sensory-motor pathways and motor neuron pools.…”
Section: Introductionmentioning
confidence: 99%
“…TSCS at T11 and L1 vertebral levels of proximal and distal motor pools in paralyzed subjects are facilitated [24]. This effect is evident in spinal motor evoked potentials of proximal and distal leg muscles to single stimulation pulses [23]. We have found that epidural SCS combined with training can increase hand grip force in spinal patients with cervical injuries [18].…”
Section: Discussionmentioning
confidence: 75%
“…Center of pressure stabilization and decrease of the pathological body forward inclination were observed. The effect may be connected with the activation of motor pools of muscles involved in maintaining the upright by TSCS [23]. Another reason --increase of strength of many muscles by FES and by this body weight support in upright posture was facilitated [8].…”
Section: Discussionmentioning
confidence: 99%